O impacto das receitas no Indice de Desenvolvimento Humano (IDH) dos municípios do Estado do Ceará - Albuquerque Junior, José Alberto Alves de (2004)
The objective of this paper is to assess the aspect of the municipal revenues in calculating the Human Development Index (HDI). First, an explanation is given on the Gini Index showing the real possibility for a country to grow economically without necessarily promoting the distribution of income. A judgement is also made on the HDI, showing how to calculate it as well as an analysis of numbers of some countries, of Brazil, including a more detailed analysis of the municipalities in the State of Ceará. In an empirical study of Ceará’s municipalities, an econometric model is used based on the 1995 to 1999 municipalities’ revenues. With that mode we conclude that the impact of a shock in the municipal revenue is more intensely felt in those municipalities that have a higher HDI and in the years farther away from the index measuring. Hence, we can say that the improvement in the HDI is related to medium and long-term policies so that there is a maturation period to obtain results and this should be a concern of the public rulers.